2020
DOI: 10.1002/alz.12184
|View full text |Cite
|
Sign up to set email alerts
|

Self‐reported obstructive sleep apnea, amyloid and tau burden, and Alzheimer's disease time‐dependent progression

Abstract: Introduction Obstructive sleep apnea (OSA) is associated with Alzheimer's disease (AD) biomarkers in cognitively normal (CN) and mild cognitive impaired (MCI) participants. However, independent and combined effects of OSA, amyloid beta (Aβ) and tau‐accumulation on AD time‐dependent progression risk is unclear. Methods Study participants grouped by biomarker profile, as described by the A/T/N scheme, where “A” refers to aggregated Aβ, “T” aggregated tau, and “N” to neurodegeneration, included 258 CN (OSA‐positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 65 publications
1
27
1
Order By: Relevance
“…Aberrant accumulation of amyloid peptides and aggregation of phosphorylated Tau protein are the major pathogenic factors in the development and progression of Alzheimer's disease 3,8 . Studies in mouse models of Alzheimer's disease and in humans have convincingly demonstrated a tight association between sleep disorder and Alzheimer's disease in terms of amyloid peptides and Tau proteins 14,15,[43][44][45][46] . Increased cerebrospinal fluid and blood levels of amyloid peptides and phosphorylated Tau protein were reported in patients with sleep disturbances 9,16,17,[47][48][49] and have been considered as biomarkers for disease progression 11 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aberrant accumulation of amyloid peptides and aggregation of phosphorylated Tau protein are the major pathogenic factors in the development and progression of Alzheimer's disease 3,8 . Studies in mouse models of Alzheimer's disease and in humans have convincingly demonstrated a tight association between sleep disorder and Alzheimer's disease in terms of amyloid peptides and Tau proteins 14,15,[43][44][45][46] . Increased cerebrospinal fluid and blood levels of amyloid peptides and phosphorylated Tau protein were reported in patients with sleep disturbances 9,16,17,[47][48][49] and have been considered as biomarkers for disease progression 11 .…”
Section: Discussionmentioning
confidence: 99%
“…These sleep behavior changes began in the prodromal phase of Alzheimer's disease while patients only suffered from mild cognitive impairment, possibly due to amyloid/Tau pathology before cognition decline 14 . Recent studies showed that sleep deprivation or disturbances increased A peptides and Tau proteins in CSF solution compared to normal sleep controls 9,[15][16][17] due to elevated production of A peptides 18 , which was supported by studies from transgenic mouse models of Alzheimer's disease 19 . On the other hand, a healthy sleep cycle was shown to facilitate A clearance from the brain tissue 20 .…”
Section: Introductionmentioning
confidence: 90%
“…In the other direction, OSA has been proposed as a risk factor for AD as it promotes or enhances AD-related subclinical pathological processes. In fact, multiple recent studies based on large cohorts have shown that subjects with OSA are, depending on the study, between 1.49 and 2.21 times more likely to develop AD than individuals not suffering from OSA [16,17,[39][40][41]. Furthermore, Bubu et al (2021) showed that individuals with OSA have shorter progression times between cognitively normal (CN) to mild cognitive impairment (MCI) or MCI to AD [17].…”
Section: Sleep Apnoea and Alzheimer's Dementiamentioning
confidence: 99%
“…In fact, multiple recent studies based on large cohorts have shown that subjects with OSA are, depending on the study, between 1.49 and 2.21 times more likely to develop AD than individuals not suffering from OSA [16,17,[39][40][41]. Furthermore, Bubu et al (2021) showed that individuals with OSA have shorter progression times between cognitively normal (CN) to mild cognitive impairment (MCI) or MCI to AD [17]. One proposed mechanism through which OSA could have an effect on AD pathology is via a dysregulation of the Aβ metabolism caused by intermittent hypoxia and reduced clearance from interstitial to cerebrospinal fluid (CSF) caused by sleep fragmentation, resulting in decreased CSF Aβ 40 and 42 levels and increased Aβ plaque formation.…”
Section: Sleep Apnoea and Alzheimer's Dementiamentioning
confidence: 99%
See 1 more Smart Citation